Use of Isothermal and Isoperibolic Calorimetry to Study the Effect of Zinc on Hydration of Cement Blended with Fly Ash - Šiler, Pavel (Materials (Basel), 2020)
Increasing utilization of secondary raw materials and alternative fuels results in increasing contents of metals in cements. Zinc is one of these elements. It comes to cement with secondary raw materials such as slag or fly ash or by the utilization of used tires as an alternative fuel. Zinc ions significantly prolong the hydration process in cement. This work deals with the influence of zinc ions in the form of very poorly soluble ZnO salt and easily soluble ZnCl(2) and Zn(NO(3))(2) on the hydration of cement blended with fly ash. Zinc was dosed in the range of 0.05%, 0.1%, 0.5% and 1% of cement weight. The effect of zinc on hydration was monitored by isothermal and isoperibolic calorimetry. A 15% addition of fly ash to cement mainly causes further retardation of hydration reactions due to the reactions of fly ash particles with Ca(2+) ions from cement. The strongest effect on the hydration retardation from all investigated compounds showed in ZnO as it dissolves very slowly. On the contrary, for the dosage of 1% of zinc in the form of ZnCl(2) significant acceleration of hydration occurred. In this work, a synergistic effect on the prolongation of hydration with a combination of cement, zinc and fly ash was demonstrated. The lengths of induction periods were assessed from detected calorimetric curves and from these lengths the curves were gained by fitting with the exponential function. Final products were next analyzed using X-ray diffraction.